LEARNING STYLE RELATIONSHIP WITH SD STUDENT'S CRITICAL THINKING ABILITY - Khotimah, Khusnul; Purwanti, Eko (Elementary School Teacher, 2020)
This study focused on the problems in teaching tenses to Primary School Teacher Education Department (PGSD), Faculty of Education, Semarang State University (UNNES). There were some of the problematic and confusing tenses such as simple tense and present perfect tense, present continuous and present simple, past simple and past continuous tense. This research used qualitative approach. It was conducted in PGSD Department, Faculty of Education, Semarang State University in 2015 by involving 120 students as the samples. The researcher used questionnaire, interview sheet, and test items as the instruments. The data were analyzed by using the descriptive method. Besides that teaching grammar had been handled throughout this study with the data obtained from the written exams of the learners. Most frequently occurred errors were listed and they were analyzed in details. The findings revealed that the reasons for these errors mostly derived from mother tongue interference and lacked of adequate linguistic background. The other component of this article was to offer remedial teaching activities for foreign language learners to compensate the shortcomings. This research aidmed to examine the correlation between learning style to student's critical thinking skills of elementary school Jekulo Subdistrict, Kudus Regency. This research used quantitative app approach type of correlation research. The subjects of this research were 4th grade students in elementary school. The sample technique was purposive sampling of 128 participants. The data collection instruments used observation, interview, questionaire, test, and document data. The data analysis technique used descriptive statistical analysis, prerequisite test analysis and final data analysis. The resullts showed that there are positive and significant correlation between learning style to students critical thining skills of elementary school, the correlation coefficient value was 0.634 in the strong category.